Artefacts Commemorating the Battle of Varna in 1444 - Lech Jaczynowski (Jan Długosz University in Częstochowa, 2020)
We just have the 575th anniversary of the memorable battle between a coalition of Christian armies and the army of the Ottoman Empire. Christians' defeat had significant consequences not only for Bulgaria, but also for Byzantium and whole Europe. The aim of the presented work is a systematization of knowledge about artefacts paying homage to the Polish-Hungarian King Ladislaus III of Varna, who fell there, and thousands of knights of both sides of the fight. There has been applied participant observation of places commemorating those events, there were conducted interviews with persons preserving their memory, there were analyzed many academic dissertations, popular scientific works and other informative materials dedicated to that topic, there were gathered data about authors of works dedicated to that Battle of nations, aiming at creation of a relatively complete description of a marketing product for needs of cultural tourism. Since many artefacts commemorating the battle do not exist anymore or exist in undocumented legends, they were separated from description of those ones which exist and can be presented to tourists interested in them. Thus, the text describes in the chronological order Turkish memorabilia, Hungarian and Polish artifacts and their authors.